2020
DOI: 10.1111/cfs.12740
|View full text |Cite
|
Sign up to set email alerts
|

Exploring drivers of demand for child protection services in an English local authority

Abstract: This paper reports on an empirical study of child protection services in a local authority where rates of investigations and interventions rose to unprecedented levels during the course of a single year.The aim of the research was to explore explanations for this rise in demand among the providers of children's social care in the area. Using an interpretative qualitative design, a series of focus groups and interviews were carried out with practitioners and managers (n=25) from statutory services and Early Hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The former might include specific interventions like parenting programmes, such as 'Triple-P' (Sanders, 2008) and the latter might include community development social work (Jack & Gill, 2010). Hood, et al (2020b) found that early help services had shifted towards more complex forms of 'late-early' intervention as a response to funding cuts, diminishing the capacity of local authorities to resolve more universal needs. This shift away from open-door provision has been reported nationally (Action for Children, 2020).…”
Section: Socioeconomic Determinants Of Incidencementioning
confidence: 99%
“…The former might include specific interventions like parenting programmes, such as 'Triple-P' (Sanders, 2008) and the latter might include community development social work (Jack & Gill, 2010). Hood, et al (2020b) found that early help services had shifted towards more complex forms of 'late-early' intervention as a response to funding cuts, diminishing the capacity of local authorities to resolve more universal needs. This shift away from open-door provision has been reported nationally (Action for Children, 2020).…”
Section: Socioeconomic Determinants Of Incidencementioning
confidence: 99%
“…Though there is no way to establish the size of reductions to the provision of services with experimental evidence against those without, the case of children's centres in England may serve as one example due to their area-based implementation, universality, and provision of multiple varied services. Smith, et al (2018) report that between 2009 and 2017 more than 30 per cent of registered children's centres had closed and 55 per cent of local authorities reported reduced services, with increased focus on specialist provision for complex needs and reduced universal support (see also : Hood, et al 2020b).…”
Section: 'What Work?' and The Defence Of Ordinary Helpmentioning
confidence: 99%
“…, $ = -0.007 [-0.013, -0.0005]). This may reflect decreasing need at a national level over time, but based on existing evidence may more likely reflect higher CIN thresholds related to rationing of services (Devaney, 2019, Hood, et al 2020a, 2020b, Smith, et al 2018. Lastly, the ALT-SR model tests for correlations between trends that are not already attributable to IMD score.…”
Section: Trends In Spend and Cin Trajectories Over Timementioning
confidence: 99%
See 1 more Smart Citation
“…For example, what proportion of a national budget goes to preventive services as opposed to statutory services, or to what extent Indigenous people can access resources and power to create independent services. Bywaters et al (2019) and Webb et al, (2020) for example found that the inequalities relating to family deprivation were the largest effect on outcomes, although other institutional level factors did have an effect, while Hood et al (2020) found through qualitative methods that cuts to community services and a more pro-active attitude to child neglect were key drivers of demand from 'external' factors. Understanding how these are produced by the political decisions of the day are key to a complex understanding of how decision outcomes happen.…”
Section: How Critical and Qualitative Approaches Can Help Extend The Dmementioning
confidence: 99%